Pendampingan Masyarakat Desa dalam Membangun Kesadaran Mendaftarkan Tanah Hak Milik (Penyuluhan Hukum di Desa Buntulia Utara Kec. Buntulia Kab. Pohuwato) - Nirwan Junus; Karlin Z. Mamu; Dian Ekawaty Ismail; Fence M Wantu; Mohamad Rusdiyanto U Puluhulawa; Dolot Alhasni Bakung; Julius T. Mandjo; Nuvazria Achir; Zamroni Abdusamad; Suwitno Yutye Imran (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The problem of land ownership in Buntulia Village is influenced by the lack of knowledge and awareness of the community about land ownership rights because of the total population of 549 families, 463 people have not registered their own land. This of course raises a fairly basic problem by the village government to be resolved. Therefore, in this downstreaming, the service team provides understanding and legal knowledge to the community about the importance of registering property rights and providing assistance to the community together with the Land Agency through the Border Marks Post Community Movement (GEMA PATAS) in order to increase community participation in installing boundary markings, making it easier for BPN officers to take measurements, as well as being able to accelerate the government program on Complete Systematic Land Registration. Thus the community could see the importance of legalizing property rights to the land in order to avoid disputes and thereby give legal certainty to the parties.